Prophecy and the church an examination of the claim of dispensationalists that the Christian church is a mystery parenthesiswhich interrupts the fulfilment to Israel of the kingdom prophecies of the Old Testament - Allis, Oswald Thompson, 1880-1973 (Philadelphia, PA Presbyterian and Reformed, 1964)
Includes bibliographical references and index.
First editions published 1945 and 1947.
Keywords: Dispensationalism -- critical appraisal; Church -- biblical teaching